Urban microclusters and tourism governance in Salvador/BA - Carolina Spinola; Jorge Antonio Silva (European Regional Science Association (ERSA), 2015)
The research that led to this article sought to analyze under what conditions the concept of tourism cluster could be applied in setting up a governance and development model for the activity in the city of Salvador, Bahia. Third leisure destination and the first capital of Brazil, Salvador has lost competitiveness to other cities in the northeast of Brazil much due to not having a governance system capable of establishing clear objectives and strategies for the destination. Starting from a broad literature review on the implementation of tourism and urban models of productive agglomerations, we performed a historical and cultural city zoning identifying a set of 6 microclusters that, by their identity aspects, were likely to be constitute a proposal for territorial organization of tourism in the city. Through field research, the feasibility of this proposal was tested, verifying the existence of the necessary conditions for the implementation of the suggested model, the research interviewed 32 experts linked to touristic trade and, based on a sampling error of 5%, 415 residents and 398 businesses in the areas studied. It was concluded that, with respect to the characteristics that define a tourist microcluster, starting by the local and limited geographical scope, the proposed sub-areas presented to respondents was supported by the opinion of the majority of them, that the neighborhoods have some kind of similarity with yours, and therefore, have an identity that unites them, forming a region with its own characteristics. The stock of intangible capital is unevenly distributed and the disparity of this indicator among the regions surveyed suggests that the difficulties in implementing local governance systems will also be unevenly distributed. Trade relations, as well as all network relationships are fragile or non-existent. There is not a sufficient level of diversification to ensure full compliance with the needs of tourists in these sub-areas, notably with regard to the possibility of accommodation and entertainment and infrastructural deficiencies are felt by all. Given all that has been pointed out, it is concluded that there is much to do to be successful the proposed regionalization of the city and its division into urban microclusters, as proposed. Creating tours and creative cultural itineraries territorially delimited, as suggested here, in a participatory manner, involving community residents and local businesses in their design and operation, however, can be a useful starting point.
Keywords: L8; R1; O1; 330; Clusters; Tourism; Governance